CHOROIDAL STRUCTURAL CHANGES AND VASCULARITY INDEX IN STARGARDT DISEASE ON SWEPT SOURCE OPTICAL COHERENCE TOMOGRAPHY. Issue 12 (December 2018) - Ratra, Dhanashree; Tan, Roy; Jaishankar, Durgasri; Khandelwal, Neha; Gupta, Arushi; Chhablani, Jay; Agrawal, Rupesh
Abstract : Purpose: To evaluate structural changes in the choroid of patients with Stargardt disease using swept source optical coherence tomography scans. Methods: A retrospective comparison cohort study was conducted on 39 patients with Stargardt disease, and on 25 age and gender matched-healthy controls. Subfoveal choroidal thickness (SFCT) was computed from the swept source optical coherence tomography machine, and the scans were binarized into luminal area and stromal areas, which were then used to derive choroidal vascularity index (CVI). Choroidal vascularity index and SFCT were analyzed independently using linear mixed effects model. Results: There was no significant difference in SFCT between the 2 groups (347.20 ± 13.61 μ m in Stargardt disease vs. 333.09 ± 18.96 μ m in the control group, P = 0.548). There was a significant decrease in the CVI among eyes with Stargardt disease as compared with the normal eyes (62.51 ± 0.25% vs. 65.45 ± 0.29%, P < 0.001). There was a negative association between visual acuity and CVI (correlation coefficient = −0.75, P < 0.001) and a positive association between visual acuity and SFCT (correlation coefficient = 0.21, P = 0.035). Conclusion: Choroidal vascularity index appears to be a more robust tool compared with SFCT for choroidal changes in Stargardt disease. Choroidal vascularity index can possibly be used as a surrogate marker for disease monitoring. A decrease in CVI was associated with a decrease in visual function in eyes with Stargardt disease. Abstract : Choroidal vascularity index can provide novel insight into structural changes in the choroid in patients with Stargardt disease.